Coffee Consumption, General Obesity and Abdominal Obesity in Adults: A Systematic Review and Meta-Analysis of Cross-Sectional Studies - Mohammad Nemati; Sanaz Soltani; Fatemeh Almasi; Asma Salari-Moghaddam; Bagher Larijani; Armin Ebrahimzadeh; Alireza Milajerdi; Ahmad Esmaillzadeh (Advanced Biomedical Research)
Background: Findings from cross-sectional studies on the association between coffee consumption and odds of obesity are inconsistent. We aimed to perform a meta-analysis of earlier cross-sectional studies on the association between coffee consumption and odds of obesity. Materials and Methods: The online databases of PubMed, ISI Web of Science, Scopus, Science Direct, and EMBASE were systematically searched to identify relevant publications up to April 2023. Cross-sectional studies that considered coffee as the exposure and general and abdominal obesity as the outcome were included. Studies that had reported odds ratios (ORs) as effect size were included in the meta-analysis. To pool data, a random-effects model was used. Results: In total, 23 studies were included in our systematic review. Twelve publications on general obesity and 15 publications on abdominal obesity were examined in the meta-analysis. Overall, 207551 individuals aged ≥19 years were included. With regards to general obesity, pooling 13 effect sizes from 12 cross-sectional studies showed that coffee intake was not associated with odds of general obesity (overall OR: 1.11; 95% CI: 0.92, 1.33). In subgroup analysis by gender, we found a significant positive association between coffee consumption and odds of general obesity in women (OR: 1.84; 95% CI: 1.51, 2.24). Concerning abdominal obesity, combining 18 effect sizes from 15 studies, we failed to find a significant association between coffee consumption and odds of abdominal obesity (OR: 1.03; 95% CI: 0.92, 1.15). Conclusion: No significant association was found between coffee intake and odds of obesity. However, gender-stratified analyses revealed significant relationships.